Mitochondrial DNA lesions and copy number are strain dependent in endurance‐trained mice - Heather L. Vellers (Physiological Reports, 2020)
Abstract In this pilot work, we selected two inbred strains that respond well to endurance training (ET) (FVB/NJ, and SJL/J strains), and two strains that respond poorly (BALB/cByJ and NZW/LacJ), to determine the effect of a standardized ET treadmill program on mitochondrial and nuclear DNA (nucDNA) integrity, and mitochondrial DNA (mtDNA) copy number. DNA was isolated from plantaris muscles (n = 37) and a gene‐specific quantitative PCR‐based assay was used to measure DNA lesions and mtDNA copy number. Mean mtDNA lesions were not different within strains in the sedentary or exercise‐trained states. However, mtDNA lesions were significantly higher in trained low‐responding NZW/LacJ mice (0.24 ± 0.06 mtDNA lesions/10 Kb) compared to high‐responding strains (mtDNA lesions/10 Kb: FVB/NJ = 0.11 ± 0.01, p = .049; SJL/J = 0.04 ± 0.02; p = .003). ET did not alter mean mtDNA copy numbers for any strain, although both sedentary and trained FVB/NJ mice had significantly higher mtDNA copies (99,890 ± 4,884 mtDNA copies) compared to low‐responding strains (mtDNA copies: BALB/cByJ = 69,744 ± 4,675; NZW/LacJ = 65,687 ± 5,180; p < .001). ET did not change nucDNA lesions for any strain, however, SJL/J had the lowest mean nucDNA lesions (3.5 ± 0.14 nucDNA lesions/6.5 Kb) compared to all other strains (nucDNA lesions/6.5 Kb: FVB/NJ = 4.4 ± 0.11; BALB/cByJ = 4.7 ± 0.09; NZW/LacJ = 4.4 ± 0.11; p < .0001). Our results demonstrate strain differences in plantaris muscle mtDNA lesions in ET mice and, independent of condition, differences in mean mtDNA copy and nucDNA lesions between strains.